Characterization of a DNA Adenine Methyltransferase Gene of Borrelia hermsii and Its Dispensability for Murine Infection and Persistence. - Allison E James; Artem S Rogovskyy; Michael A Crowley; Troy Bankhead (PLoS ONE, 2016)
DNA methyltransferases have been implicated in the regulation of virulence genes in a number of pathogens. Relapsing fever Borrelia species harbor a conserved, putative DNA methyltransferase gene on their chromosome, while no such ortholog can be found in the annotated genome of the Lyme disease agent, Borrelia burgdorferi. In the relapsing fever species Borrelia hermsii, the locus bh0463A encodes this putative DNA adenine methyltransferase (dam). To verify the function of the BH0463A protein product as a Dam, the gene was cloned into a Dam-deficient strain of Escherichia coli. Restriction fragment analysis subsequently demonstrated that complementation of this E. coli mutant with bh0463A restored adenine methylation, verifying bh0463A as a Dam. The requirement of bh0463A for B. hermsii viability, infectivity, and persistence was then investigated by genetically disrupting the gene. The dam- mutant was capable of infecting immunocompetent mice, and the mean level of spirochetemia in immunocompetent mice was not significantly different from wild type B. hermsii. Collectively, the data indicate that dam is dispensable for B. hermsii viability, infectivity, and persistence.